Climate-induced vulnerabilities: Participatory assessment for My Loi village, Ky Son commune, Ky Anh district, Ha Tinh province - Simelton, Elisabeth; Hai, Le Van; Tuan, Duong Minh; Le Dinh Hoa (2017)
This vulnerability assessment was conducted for the project “Generating evidence base for upscaling local adaptation through Climate-Smart Agriculture” under the CGIAR Research Program Climate Change, Agriculture and Food Security (CCAFS). This report covers the My Loi climate-smart village (CSV) project site in Vietnam. A separate study is conducted for the sites in the Philippines. The main purpose of this paper is to document evidences of exposure, impacts, and vulnerability. The results of this study will help in forming other CCAFS projects in the CSV, and these will be continuously updated throughout the project.